Learning style preferences of internal medicine residents and in-training examination scores: is there a correlation?. Issue 5 (3rd September 2021) - Muganlinskaya, Nargiz; Mollaeian, Arash; Karpman, Mitchell
ABSTRACT: The internal medicine in-training examination (IM-ITE) has been traditionally used as a measuring tool to evaluate the base of knowledge of the residents in internal medicine residency programs across the US. Multiple interventions has been applied and studied to increase the first-time passing rate of ABIM, as it is an indicator of each residency program's performance and ranking. Additionally, studies have demonstrated that different learning styles and preferences are a predictor of exam results; however, it is not well known whether certain preferred learning styles are correlated with certain IM-ITE results. Primary objective of our study was to find a correlation between residents' preferred learning style, based on Kolb learning style inventory, and their PGY1 and PGY2 IM-ITE performance score difference. Secondary objective was to find the correlation between PGY2s' IM-ITE score and their preferred learning styles based on the Kolb learning style inventory. Mean scores of PGY1 and PGY2 IM-ITE were compared in each learning style group. Additionally, the mean difference between the PGY1 and PGY2 IM-ITE scores for each learning group was compared as well. The analysis of the mean IM-ITE score from PGY1 to PGY2 between groups revealed a statistically significant improvement in IM-ITE score from PGY1 to PGY2 in all groups, however, with a larger difference in one of the groups.